Implementasi Kriptografi AES untuk Keamanan Pengiriman Data Internet of Things Menggunakan Web Service Rest pada NodeMCU - Afrijal Rizqi Ramadan; Ardito Wahyu Prakoso; Ghifari Dwi C (Systemic: Information System and Informatics Journal, 2020)
The emergence of the term Internet of Things in this era generally has a positive role for humans in various aspects such as health, industry, cities and even agriculture. However, there is a problem that is a serious threat in the IoT environment, namely data security. Data security is something that is required in storing or sending important information. It is dangerous if the data falls and is taken by parties who will be used irresponsibly who can later retrieve and even change the actual data. Therefore, the use of AES cryptography is needed to solve this problem. AES stands for Advanced Encryption Standard is a symmetric key encryption algorithm that has a faster data security process than an asymmetric algorithm. The purpose of this study is to describe how to apply the AES algorithm to IoT devices as an effort to secure data. Data in the form of temperature and humidity values ​​are encrypted by the AES algorithm before being sent to the database server with a container in the form of a wireless network or called wifi. In the web server, encrypted data is returned in the form of the original data before entering the database. The results of this test are to confirm that the system is running optimally. The use of the AES algorithm is declared successful in meeting the objectives, namely for data security and confidentiality.